Infections among Contacts of Patients with Nipah Virus, India - Kumar, C.P. Girish; Sugunan, Attayur P.; Yadav, Pragya; Kurup, Karishma Krishna; Aarathee, Renjith; Manickam, Ponnaiah; Bhatnagar, Tarun; Radhakrishnan, Chandni; Thomas, Beena; Kumar, Akhilesh; Jayasree, Jayasree; Philomina, Bina; et al. (Emerging infectious diseases, 2019)
We conducted a serosurvey of 155 healthcare workers and 124 household and community members who had close contact with 18 patients who had laboratory-confirmed Nipah virus infections in Kerala, India. We detected 3 subclinical infections; 2 persons had IgM and IgG and 1 only IgM against Nipah virus.